Perancangan Sistem Penyisipan Pesan pada Gambar dengan Metode Least Significant Bit (LSB) Berbasis Website - I Wayan Dimas Wirahadi Saputra; I Gede Santi Astawa (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2024)
The advancement of digital communication and the need for secure information exchange have led to the development of various techniques for data hiding and steganography. One of the widely used methods is the Least Significant Bit (LSB) technique, which allows the embedding of secret messages within digital images without perceptible visual changes. In this paper, we present the design and implementation of a message embedding system based on LSB method, integrated into a web-based platform. The proposed system provides a user-friendly interface for selecting an image and entering a secret message to be embedded. Utilizing HTML5 canvas and JavaScript, the system processes the selected image, extracts the LSB of each pixel, and replaces it with the corresponding bits of the secret message. The resulting image with the hidden message is then displayed to the user. Furthermore, the system offers the capability to extract the hidden message from an image previously processed by the system. The web-based nature of the system allows for easy accessibility and usage across different devices without the need for additional software installations. It provides a practical and interactive environment for users to experiment with message embedding techniques, thereby fostering understanding and awareness of data security issues. The experimental results demonstrate the effectiveness and efficiency of the system in embedding and extracting messages from various images while maintaining satisfactory visual quality. The system's user-friendly interface, combined with its robust functionality, makes it a valuable tool for users interested in secure communication and digital steganography.